SUSTAINABLE DEVELOPMENT IN TOURISM DESTINATIONS THROUGH SMART CITIES: A CASE OF URBAN PLANNING IN JAMMU CITY - Suman Lata; Aruditya Jasrotia; Swati Sharma (Enlightening Tourism: A Pathmaking Journal)
With the rapid growth of technology, the world is witnessing a change from sustainability valuation towards smart city goals in the 21st century. Cities can play an imperative role in combating and countering climate change by using novel smart technologies which would help in reducing emission of greenhouse gases and will further enhance the energy proficiency of the cities. The current study aims to understand the perception of the local residents of a tourism destination, Jammu in India, towards the effect of dimensions of the smart city on sustainable development. The hypotheses proposed in the study were validated by utilizing the SEM (Structural Equation Modeling), with the assistance of Partial Least Squares (PLS). The study found that all three dimensions (namely, smart economy, smart environment, and smart society) are significant predictors of sustainable development. The findings resulted from the data collected with the help of a questionnaire from the local residents of Jammu city which is being developed as a smart city by the government of India.